2015
DOI: 10.2337/db14-1439
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling Regulates Blood Pressure by Downregulating a GSK-3β–Mediated Pathway to Enhance Insulin Signaling in the Central Nervous System

Abstract: Aberrant Wnt signaling appears to play an important role in the onset of diabetes. Moreover, the insulin signaling pathway is defective in the nucleus tractus solitarii (NTS) of spontaneously hypertensive rats (SHRs) and fructosefed rats. Nevertheless, the relationships between Wnt signaling and the insulin pathway and the related modulation of blood pressure (BP) in the central nervous system have yet to be established. The aim of this study was to investigate the potential signaling pathways involved in Wnt-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 52 publications
(56 reference statements)
0
27
0
Order By: Relevance
“…[55] The Th1/Th2 pathway is involved in the regulation of immune responses[56] and has been linked to hypertension and atherosclerosis. [57, 58] The role of the immune system in the development of hypertension has been suggested in clinical studies and experimental animal models.…”
Section: Discussionmentioning
confidence: 99%
“…[55] The Th1/Th2 pathway is involved in the regulation of immune responses[56] and has been linked to hypertension and atherosclerosis. [57, 58] The role of the immune system in the development of hypertension has been suggested in clinical studies and experimental animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt ligands are secreted glycoproteins that signal through Frizzled (FZD) receptor and low-density lipoprotein receptor-related protein 5 or 6 (LRP5 or LRP6) co-receptor, leading to downregulation of glycogen synthase kinase-3 (GSK-3) activity and the initiation of the canonical Wnt/β-catenin signaling cascade 33, 34. Activation of canonical Wnt signaling culminates in the cytoplasmic accumulation of β-catenin and its translocation to the nucleus where it complexes with transcription factors and coactivators to drive context-dependent target gene expression 35, 36.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Wnt signaling in the NTS is defective in hypertension, as evidenced by decreased phosphorylation of LRP6 (activation) and GSK-3β (deactivation) in genetic (spontaneously hypertensive rats or SHR) and dietary (fructose fed mice) models of hypertension. It has been shown that intraventricular infusion of Wnt3a into the brains of SHR rats lowers BP, decreases heart rate, and increases nitric oxide release (59). This effect was reversed with the administration of Wnt antagonist Dickkopf-1 (DKK1) (59, 60).…”
Section: Is There a Relationship Between Wnt Signaling And Hypertementioning
confidence: 99%
“…It has been shown that intraventricular infusion of Wnt3a into the brains of SHR rats lowers BP, decreases heart rate, and increases nitric oxide release (59). This effect was reversed with the administration of Wnt antagonist Dickkopf-1 (DKK1) (59, 60). Similar results were obtained in the fructose-fed–induced hypertension model.…”
Section: Is There a Relationship Between Wnt Signaling And Hypertementioning
confidence: 99%
See 1 more Smart Citation